2015
DOI: 10.1111/jar.12177
|View full text |Cite
|
Sign up to set email alerts
|

Effects on Physical Health of a Multicomponent Programme for Overweight and Obesity for Adults with Intellectual Disabilities

Abstract: The treatment was effective in reducing overweight and obesity, improving cardiovascular capacity and therefore the physical health of the participants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
43
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(45 citation statements)
references
References 80 publications
1
43
0
1
Order By: Relevance
“…Results of this trial, and others in the literature, clearly indicate that adults with intellectual and developmental disabilities are capable of achieving clinically significant weight loss in response to multicomponent weight loss/maintenance interventions tailored to their cognitive abilities that includes an energy reduced diet, increased physical activity and behavioural strategies (Martinez‐Zaragoza et al., ; Melville et al., ; Saunders et al., ; Spanos, Melville, and Hankey ; Spanos et al., ). Interestingly, the magnitude of weight loss reported in this, and other trials in adults with intellectual and developmental disabilities, equals or exceeds that of the weight loss reported in trials conducted in the general population.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Results of this trial, and others in the literature, clearly indicate that adults with intellectual and developmental disabilities are capable of achieving clinically significant weight loss in response to multicomponent weight loss/maintenance interventions tailored to their cognitive abilities that includes an energy reduced diet, increased physical activity and behavioural strategies (Martinez‐Zaragoza et al., ; Melville et al., ; Saunders et al., ; Spanos, Melville, and Hankey ; Spanos et al., ). Interestingly, the magnitude of weight loss reported in this, and other trials in adults with intellectual and developmental disabilities, equals or exceeds that of the weight loss reported in trials conducted in the general population.…”
Section: Discussionmentioning
confidence: 70%
“…None of the trials described in the Spanos review included a long‐term (≥1 year) comprehensive weight maintenance programme as recommended by current clinical guidelines (Jensen et al., ). Publications subsequent to the Spanos review (Spanos, Melville, and Hankey ) have demonstrated the effectiveness of a 1‐year weight maintenance intervention in a small sample ( n = 28) of adults with intellectual and developmental disabilities who achieved ≥3% weight loss over 16 weeks (Spanos, Hankey, & Melville, ) and clinically significant weight loss (~8 kg) in a sample of 33 adults with intellectual and developmental disabilities attending a community occupational therapy day centre, in response to a 17‐week intervention consisting of reduced energy intake, physical activity and a token economy motivational system (Martinez‐Zaragoza, Campillo‐Martinez, & Ato‐Garcia, ). Pett et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence suggests that adults with intellectual disabilities tend to have poorer health than the general population (Cocks, Thomson, Thoresen, Parsons, & Rosenwax, ; Cooper et al., ; Emerson, ; Martínez‐Zaragoza, Campillo‐Martínez, & Ato‐García, ). They also lead more sedentary and less physically active lifestyles (Bergstrom, Hagstromer, Hagberg, & Elinder, ; Dairo, Collett, Dawes, & Oskrochi, ; Finalyson, Turner, & Granat, ; Temple, ; Temple & Walkley, ) and have higher rates of obesity (Bhaumik, Watson, Thorp, Tyrer, & McGrother, ; Melville et al., , ).…”
Section: Introductionmentioning
confidence: 99%
“…Most research has been conducted on subjects with psychiatric problems rather than on young neurologically disabled patients [1, 2, 21, 22]. On the basis of anecdotal observations, it is suspected that this population is at greater risk for MS and preclinical cardiovascular events.…”
Section: Discussionmentioning
confidence: 99%